2014
DOI: 10.1016/j.surg.2013.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted ablation of pilonidal sinus: A new minimally invasive treatment—A pilot study

Abstract: Our results are encouraging and suggest that this technique may offer a very effective way to treat pilonidal sinus. Further studies are necessary to validate its use in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 11 publications
1
52
0
2
Order By: Relevance
“…Minimally invasive treatment has many advantages. Several studies have shown that the period off work after EPSiT is shorter than after more extensive operations . Such patients also tend to experience less pain and better quality of life after endoscopic operation for pilonidal sinus than after classic flap surgery .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive treatment has many advantages. Several studies have shown that the period off work after EPSiT is shorter than after more extensive operations . Such patients also tend to experience less pain and better quality of life after endoscopic operation for pilonidal sinus than after classic flap surgery .…”
Section: Discussionmentioning
confidence: 99%
“…EPSiT is shorter than after more extensive operations [13][14][15][16][17][18]. Such patients also tend to experience less pain and better quality of life after endoscopic operation for pilonidal sinus [11] than after classic flap surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid healing of the lesion, thanks to the rich blood supply to the face, after adequate excision and curettage, is to be expected 3 4. In recent years, minimally invasive treatment techniques such as endoscopic or video-assisted ablation of pilonidal sinuses have been introduced 11. However, because of the superficial location of the pilonidal sinus in our case, we did not find the need for these techniques.…”
Section: Discussionmentioning
confidence: 62%
“…The noticeable surgical scar resulting after skin flap creation might be one reason that patients prefer a non-invasive method. A recent study of the VADA method, which also offers a good opportunity to clean up hair and debris from the SPD cavity under direct vision, reported 3.7% recurrence after 1 year of follow-up 5. In contrast, CPA never provides an optimal opportunity to clean up the cavity.…”
Section: Discussionmentioning
confidence: 99%